High Frequency MOSFET Gate Drivers. - Zhang, ZhiLiang (Materials, Circuits and Devices, 2017)
This book describes high frequency power MOSFET gate driver technologies, including gate drivers for GaN HEMTs, which have great potential in the next generation of switching power converters. Gate drivers serve as a critical role between control and power devices. In recent years, there has been a trend to increase the switching frequency beyond multi-MHz in switching power converters to reduce the passive components and significantly improve power density. However, this results in high switching loss and gate driver loss in power MOSFETs. The novel approach in this book is the proposed Current Source Gate Driver (CSD) including different topologies, control and applications. The CSD can reduce the switching transition time and switching loss significantly, and recover high frequency gate driver loss compared to conventional voltage gate drivers. The basic idea can also be extended to other power devices to improve high frequency switching performance such as SiC MOSFET and IGBT. Topics covered in the book include the state-of-the-art of power MOSFET drive techniques, the switching loss model, current source gate drivers (CSDs), resonant gate drivers, adaptive gate drivers and GaN HEMT gate drivers. The book is essential reading for design engineers, researchers and advanced students working in switching power supplies and in power electronics generally.